2019
DOI: 10.1002/jcp.28329
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Adipose‐derived mesenchymal stem cells ameliorate the inflammatory reaction in CLP‐induced septic acute lung injury rats via sTNFR1

Abstract: We hypothesized that the adipose‐derived mesenchymal stem cells (ADMSCs), which secrete high amounts of soluble molecules, such as soluble tumor necrosis factor receptor 1 (sTNFR1), may ameliorate sepsis‐induced acute lung injury (ALI). A total of 120 male adult Sprague–Dawley rats were separated into four groups: the sham control (SC), sepsis induced by cecal ligation and puncture (CLP), CLP–ADMSCs, and CLP–sTNFR1 small interfering RNA (siRNA) groups; CLP groups underwent CLP and then received 1 × 106 ADMSCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
6
14
0
Order By: Relevance
“…Intervention with ADMSCs reduced organ damage, as well as inflammatory infiltration and hemorrhage, in the lungs, and the diversity of the flora and the content of pathogenic bacteria in rats with sepsis increased significantly. In addition, we found that treatment with ADMSCs also reduced the expression of pro-inflammatory factors, such as TNF-α and IL-6, which is consistent with our previous studies [49,50] .…”
Section: Discussionsupporting
confidence: 92%
“…Intervention with ADMSCs reduced organ damage, as well as inflammatory infiltration and hemorrhage, in the lungs, and the diversity of the flora and the content of pathogenic bacteria in rats with sepsis increased significantly. In addition, we found that treatment with ADMSCs also reduced the expression of pro-inflammatory factors, such as TNF-α and IL-6, which is consistent with our previous studies [49,50] .…”
Section: Discussionsupporting
confidence: 92%
“…A previous meta-analysis [42] collected and evaluated preclinical evidence regarding the use of MSCs in animal models of sepsis and demonstrated that MSC therapy could reduce the odds of death. The updated meta-analysis presented here includes another seven high-quality studies [27,[29][30][31][32][33]41] that were mainly published in recent 3 years, and confirms the potential therapeutic efficacy of MSCs for reducing the mortality rate of sepsis in animal models, thus, providing possibilities for MSC therapy in preclinical studies of sepsis. To our knowledge, two small clinical phase 1 trials [43,44] have been performed to evaluate the safety and feasibility of MSC therapy in sepsis and septic shock patients.…”
Section: Discussionsupporting
confidence: 63%
“…Firstly, our study provides an up-to-date meta-analysis of the effectiveness of MSCs in sepsis animal models. Although a previously published metaanalysis [42] assessed the effectiveness of MSCs in sepsis animal models, the meta-analysis presented here includes seven recently published high-quality studies [27,[29][30][31][32][33]41]. Out of all the included studies, only one study showed no positive effect of MSC therapy on sepsis animal models (OR=2.78, 95% CI 0.66-11.62, P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis [38] collected and evaluated preclinical evidence regarding the use of MSCs in animal models of sepsis and demonstrated that MSC therapy could reduce the odds of death. The updated meta-analysis presented here includes another seven high-quality studies [27,36,37,[39][40][41][42] that were mainly published in the last three years, and confirms the potential therapeutic efficacy of MSCs for reducing the mortality rate of sepsis in animal models, thus, providing possibilities for MSC therapy in preclinical studies of sepsis. To our knowledge, two small clinical phase 1 trials [43,44] have been performed to evaluate the safety and feasibility of MSC therapy in sepsis and septic shock patients.…”
Section: Discussionsupporting
confidence: 62%
“…Firstly, our study provides an upto-date meta-analysis of the effectiveness of MSCs in sepsis animal models. Although a previously published meta-analysis [38] assessed the effectiveness of MSCs in sepsis animal models, the meta-analysis presented here includes seven recently published high-quality studies [27,36,37,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%